Ethics and Philosophy according to H. D. Thoreau - Jeřichová, Ivana (Univerzita Pardubice, 2018)
This bachelor thesis focuses on the ethics and philosophy of Transcendentalism according to perspective of well-known Transcendentalist H. D. Thoreau. It delas with Transcendentalist issues and principles and explains the cultural background which had led to the birth of Transcendentalism. The practical section illustrates the Transcendentalist principles presented in the book Walden from perspective of H. D. Thoreau who applied them into his everyday life. It also elaborates on followers of the Transcendentalist movement an on H. D. Thoreau himself.
Etika a filosofie transcendentalismu podle H. D. Thoreaua
Keywords: Thoreau, Henry David; transcendentalism; Emerson, Ralph David; Walden; nature; Thoreau, Henry David; transcendentalismus; Emerson, Ralph David; Walden; příroda